Computer model of study of hydrodynamics of irrigant in dental root canal (an experimental study) - Rozhko, Vitaliy; Godovanets, Oksana; Basista, Anastasiia; Petruniv, Volodymyr; Kogut, Volodymyr; Volokitin, Oleksii (ScienceRise: Medical Science, 2025)
Computational fluid dynamics modelling was performed to obtain additional information about the flow of irrigant in the root canal system. The interaction between the flow rate of the irrigant, the size and taper of the root canal apex, and the type, size and depth of insertion of the endodontic needle was studied. Aim. The aim of the study was to conduct an experimental study using computer modelling of the unsteady leakage of irrigation solution in the root canal. Materials and methods. Computer modelling of the unsteady leakage of irrigation solution was performed using three-dimensional Reynolds-mediated Navier-Stokes equations of continuity -Stokes equations for an incompressible viscous fluid for a position corresponding to the distance from the tip of the endodontic needle to the apical opening of the root canal - 1 mm. Results. Visualisation of the irrigant flow is presented in the form of isolines on the surfaces of the canal and in cross-sections of the calculated area, surface (boundary) and spatial flows, as well as projections of velocity vectors on the surfaces of cross-sections, and the distribution of flow parameters along the lines of the graph. Conclusions. The study showed that the location of the irrigation needle opening towards the large diameter of the root canal, hypothetically, provides a better washing capacity for the irrigation solution